Organophosphorus Poisoning Induced Delayed Poly-axonal Motor Neuropathy: A Case Report - Prasai, Pratik; Thakur, Jitendra; Tamrakar Karki, Karuna (Eastern Green Neurosurgery, 2022)
Organophosphate being the lethal compound and easily available insecticide in the developing countries has significant potential health risk. The morbidity related to organophosphate poisoning as delayed peripheral neuropathy, extra pyramidal syndromes and neuropsychiatric manifestations are still the major consequences of secondary neuronal damage. Herein, we present a case of 23 year old lady who ingested organophosphate in the context of suicidal attempt and presented with motor neuropathy after 4 weeks.